2016
DOI: 10.7554/elife.14756
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intravital imaging of the multicolor-coded tumor microenvironment during combination immunotherapy

Abstract: The combined-immunotherapy of adoptive cell therapy (ACT) and cyclophosphamide (CTX) is one of the most efficient treatments for melanoma patients. However, no synergistic effects of CTX and ACT on the spatio-temporal dynamics of immunocytes in vivo have been described. Here, we visualized key cell events in immunotherapy-elicited immunoreactions in a multicolor-coded tumor microenvironment, and then established an optimal strategy of metronomic combined-immunotherapy to enhance anti-tumor efficacy. Intravital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…It was found that the combined system outperformed the single system, and it was suitable for quantitative three‐dimensional imaging of the fluophor . Furthermore, aiming at the significant demand for the visualization research of tumor immunity, they developed multiscale optical imaging approaches , optimized red‐shift fluorescent protein probes , established multicolor labeling animal models, and achieved the in vivo visualization of specific antitumor immune response and immunotherapy .…”
Section: Selected Research Achievementsmentioning
confidence: 99%
“…It was found that the combined system outperformed the single system, and it was suitable for quantitative three‐dimensional imaging of the fluophor . Furthermore, aiming at the significant demand for the visualization research of tumor immunity, they developed multiscale optical imaging approaches , optimized red‐shift fluorescent protein probes , established multicolor labeling animal models, and achieved the in vivo visualization of specific antitumor immune response and immunotherapy .…”
Section: Selected Research Achievementsmentioning
confidence: 99%
“…However, it is unclear how these two therapies synergize and no spatio‐temporal dynamics have been described in vivo. By imaging implanted melanoma tumors, Qi et al showed that regulatory T cells form an “immunosuppressive ring” around the solid tumor that prevents infiltration by the adoptive CTLs and other anticancer immune cells . Pretreatment with CTX before ATC not only led to the removal of the immunosuppressive barrier but also promoted the accumulation of adoptive CTLs and endogenous immune cells in the tumor area.…”
Section: Translational Potential Of Iv‐mpm For Cancermentioning
confidence: 99%
“…The vast majority of them, including DNA 8,9 -and RNA [10][11][12][13] -based PCR and reverse transcription quantitative real-time PCR (RT-qPCR), species-specific transcriptome [14][15][16][17][18][19][20] and proteome 21,22 analyses as well as flow cytometry [23][24][25] , are molecular profiling approaches which require tissue dissociation or lysis and do not address host contribution in situ on a single cell level. To investigate the unperturbed interaction between the tumor and its microenvironment, the use of genetically modified cells or mouse models expressing fluorescent reporter proteins [26][27][28][29][30] might want to be avoided. Others, inluding less common DNA [31][32][33] -and RNA 34,35 -in situ hybridization as well as broadly used IHC [36][37][38][39][40][41] , do address this aspect but harbor the limitations to be either difficult to evaluate and interpret, as this is the case for in situ hybridization approaches, or to rely on mouse-specific probes or antibodies which target only one particular cell type (Fig.…”
Section: Comparison With Existing Approachesmentioning
confidence: 99%